Modelling and Interpretation of Global Lithospheric Magnetic Anomalies - Hemant, Kumar (2003)
Title page Contents, Abstract IV 1 Introduction 1 1.1 Some pertinent definitions 2 1.2 Need for the present study 2 1.3 Lithospheric field models 3 1.4 Preparation of field models 4 1.5 The objective of deriving the lithospheric field models 9 1.6 Ambiguities in interpretation 12 1.7 The present work 12 2 Global crustal magnetisation model 15 2.1 Introduction 15 2.2 Geology of the continents 16 2.3 Oceanic crust 26 2.4 Continental and island arcs 28 2.5 Phanerozoic cover 28 2.6 Modeling 29 2.7 Flowchart showing the present work 33 3 Methodology 35 3.1 Introduction 35 3.2 Equivalent dipole method 36 3.3 Nolte-Siebert method 38 3.4 Comparison of the two methods 41 3.5 Computing vertical field anomaly 42 4 Vertical field anomaly map 44 4.1 Comparison of observed and initial model vertical field anomaly map44 4.2 Examples of predicted anomalies in agreement and in disagreement with observed anomaly map 45 5 Implications for geology 68 5.1 Kentucky-Tennessee region, North America 70 5.2 North-Greenland, Greenland 72 5.3 West African Craton, West Africa 74 5.4 Bangui anomaly, Africa 76 5.5 Kolyma-Omolon block, Siberia 78 5.6 Tarim baisn, China 80 5.7 Global first iteration model 82 6 Discussion 84 6.1 Curie-temperature isotherm depth 84 6.2 Remanence 85 6.3 Continent-Ocean boundary 86 6.4 Oceanic plateaus 88 6.5 Key uncertainties 90 7 Conclusions 92 7.1 Summary 92 7.2 Outlook 95 Appendices 1-12 96 References 122 Acknowledgements 136 Curriculum vitae 137 After a gap of nearly two decades since the Magsat mission in 1980, the dedicated low-orbit potential field mission CHAMP is now in the third of its seven year mission. Already, the new magnetic total intensity and vector data have yielded maps of the global crustal field of unprecedented accuracy and resolution. Here, we assess the value of these maps to infer deep crustal structure of regions overlain by younger cover. A GIS based modelling technique has been developed to model the various geological units of the continents starting from the geological map of the ...